The knowledge dividend creating high-performance companies through value-based knowledge management - Tissen, René Johannes 1955-; Andriessen, Daniel; Deprez, Frank Lekanne (Financial Times / Prentice Hall, 2000)
How can companies prepare themselves for greater success in the knowledge economy? As the world evolves into a virtual market space, new rules for business success are imminent. Companies who gain the edge will have one notable characteristic. They use their entire knowledge base to continuously add more value to their customers and employees, and therefore, to their company as a whole. The Knowledge Dividend shows you how to initiate and leverage knowledge in accordance with your company strategy. It illustrates how to create organizations that are entirely process, team and community based, and ICT enabled. It explains, by example, how to shape the knowledge attitude and key competencies of knowledge professionals so that they are committed to the future - the company's and their own.